Mission Drift and the Sustainability of Hybrid Organizations in Extreme Institutional Contexts: The Case of a Communitarian Microfinance Institution in Brazil - Marconatto, Diego; Barin Cruz, Luciano; Aguilar Delgado, Natalia (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2020)
Hybrid organizations are those striving to balance business operations with social and environmental goals. The previous literature has largely disregarded the strategies that these organizations use to avoid mission drift, or the risk of losing sight of their social missions in their efforts to generate revenue. In this paper, we draw on the case of a communitarian bank in Brazil to investigate what strategies hybrid organizations mobilize to avoid mission drift in extreme institutional contexts. We argue that by developing the ability of “embedding within the local community”, hybrid organizations are better equipped to guarantee the sustainability of their hybrid nature.